The Relationship Between Macronutrient Intake, Physical Activity, and Nutritional Status of Production Employees at PT Eurochair Internusa - Maulidiyah Lidya; Desty Muzarafatus Sholikhah (Journal of Food, Nutrition, and Health Advances, 2026)
Nutritional status reflects the balance between nutrient intake and the body's requirements, influenced by various factors including macronutrient consumption and physical activity. This study aims to identify and analyze the relationship between energy, carbohydrate, protein, and fat intake, as well as physical activity, with employees' nutritional status. This research employed an observational analytical quantitative design with a cross-sectional approach, involving a sample of 74 respondents. Macronutrient intake was measured using a 2x24-hour food recall, and physical activity was assessed using the Baecke questionnaire, while nutritional status was measured based on Body Mass Index (BMI). Data analysis was performed using the Spearman Rank correlation test. There were significant positive correlations between energy intake and nutritional status (p = 0.003; r = 0.342), carbohydrate intake and nutritional status (p = 0.022; r = 0.266), and fat intake and nutritional status (p = 0.000; r = 0.508). The strongest positive correlation was observed between fat intake and nutritional status (r = 0.508).The strongest association was found between fat intake and nutritional status (r = 0.508). However, no significant relationship was observed between protein intake and nutritional status (p = 0.057; r = -0.222). There is a relationship between physical activity and nutritional status (p = 0.000; r = -0.798). These results indicate that the greater the intake of energy, carbohydrates, and fat, the higher the likelihood of an individual being overweight or obese.